Role of ADHD in the Co‐Occurrence Between Heavy Alcohol Use and Depression Trajectories in Adulthood. (27th December 2018) - Wang, Frances L.; Pedersen, Sarah L.; Joseph, Heather; Gnagy, Elizabeth M.; Curran, Patrick; Pelham, William E.; Molina, Brooke S. G.
Abstract : Background: Attention‐deficit/hyperactivity disorder (ADHD) is associated with greater heavy alcohol use and depressive symptoms in adulthood. Yet, few studies have investigated whether childhood ADHD predicts an increased association between heavy drinking and depression in adulthood when this co‐occurrence becomes more common. We examined associations among heavy alcohol use and depression longitudinally from ages 21 to 29 and whether these associations differed for those with or without childhood ADHD, as well as for those with or without persistent ADHD in adulthood. Methods: Data were from the Pittsburgh ADHD Longitudinal Study, a prospective cohort of children diagnosed with ADHD and demographically similar individuals without ADHD histories. ADHD symptoms in adulthood were self‐ and parent reported; depressive symptoms and frequency of drinking 5 or more drinks in a single drinking occasion were self‐reported and measured at 5 time‐points from ages 21 to 29. Depression and alcohol use were modeled in a multiple‐group, parallel process longitudinal growth model. Results: The slopes of heavy alcohol use and depression were significantly and positively associated from ages 25 to 29 but not at the younger ages. Although the strength of these associations did not differ by group (with or without ADHD, childhood or adulthood), the slopes of depression and heavy drinking at the older ages were highly variable and individuals with ADHD showed significantly faster growth in depression from ages 25 to 29. Conclusions: Due to the strengthening association between heavy drinking and depression for adults in their late 20s, and increasing depression for adults with ADHD histories, individuals with ADHD may be at greater risk for co‐occurring depression and binge drinking. Negative reinforcement‐related alcohol use may strengthen as these individuals age toward the fourth decade of life. More rigorous testing of this possibility is warranted. Abstract : We assessed whether childhood ADHD and age were associated with heightened risk for co‐occurring change in heavy drinking and depression in adulthood. Significant correlations between changes in heavy drinking and depression from ages 25 to 29, but not 21 to 25, suggested that depression plays a stronger role in heavy drinking as adults age. Although associations did not differ in strength by ADHD, there was preliminary evidence that ADHD conferred risk for parallel increases (vs. decreases) in both problems and further investigation is warranted.